Former Yugoslav Republic of Macedonia Early Childhood Development : SABER Country Report 2015 - World Bank Group (World Bank, Washington, DC, 2016)
This report presents an analysis of the Early Childhood Development (ECD) programs and policies that affect young children in Macedonia and recommendations to move forward. The Systems Approach for Better Education Results (SABER) initiative produces comparative data and knowledge on education policies and institutions, with the aim of helping countries systematically strengthen their education systems. SABER evaluates the quality of education policies against evidence-based global standards, using new diagnostic tools and detailed policy data.This report is part of a series of reports prepared by the World Bank using the Systems Approach for Better Education Results (SABER-ECD) framework and includes analysis of early learning,health, nutrition and social and child protection policies and interventions in Macedonia, along with regional and international comparisons. SABER-ECD identifies three core policy goals that countries should address to ensure optimal ECD outcomes and they are as follows: 1) establishing an enabling environment; 2)implementing widely; and 3) monitoring and assuring quality. To conclude, Macedonia has successfully established many elements of a strong ECD system, including essential healthcare and standards for early childhood education. It may need to strengthen its intersectoral coordination and finance systems. The country’s biggest challenge may be how to expand preprimary enrollment,especially to children from poor families,while maintaining quality.